Applicability of Quality Indicators for Appropriate Antibiotic use in Outpatient Parenteral Antimicrobial Therapy (OPAT): A Point Prevalence Survey - Pablo March-López; Pablo March-López; Inés Arancibia Freixa; Mireia Martinez Gil; Gastón Araujo Espinoza; Lidia Ortega Polonio; Elisabeth Cecilia Paredes; Montserrat Carrasco Sanchez; Cristina Sangrador; Júlia Pardo; Jordi Nicolás; Jordi Nicolás; et al. (Frontiers Media S.A., 2021)
The ability to measure the quality of antibiotic prescription is a critical element in any antimicrobial stewardship programme. The aim of this study was to evaluate the clinimetric properties of 33 quality indicators (QIs) developed to assess Outpatient Parenteral Antimicrobial Therapy (OPAT) and to identify potential room for improvement in a hospital-at-home (HaH) unit. Study performed in a healthcare district in Barcelona, Spain with 260,657 inhabitants, nine primary healthcare centres, a 400-bed acute care teaching hospital, and an HaH unit. We studied 33 QIs on appropriate antibiotic use and classified them as qualitative or quantitative. Quantitative QIs were further categorized as measurable or non-measurable depending on the availability of data in the patients' medical records. Data from 202 OPAT episodes in 192 patients were assessed. Adherence was found for 22 of the 24 qualitative QIs analyzed; the other two showed room for improvement. Four of the nine quantitative indicators were non-measurable. High adherence rates were achieved for QI-17 "The OPAT plan should be documented" (84.65%), QI-26 "The OPAT treatment plan should include choice, dose, frequency, duration and follow-up plan" (79.70%), and QI-33 "The team should document clinical response" (94.55%). Adverse events were documented in just 1.98% of cases (QI-32) and 92.57% patients were classified as alive on discharge (QI-24). The QIs evaluated were applicable to clinical practice and proved useful for identifying areas with room for improvement in our setting and for guiding the design of future interventions with specific objectives.